Vaginal Cytological Changes and Estrus Response Following Estrus Synchronization Using a Double Prostaglandin-F₂α and Gonadotropin Releasing Hormone in Pasundan Heifers - Rini Widyastuti; Azis, Azhar Abdul; Setiawan, Rangga; Hilmia, Nena; Lubis, Alkaustariyah; Ridlo, Muhammad Rosyid (Jurnal Veteriner, 2026)
Pasundan cattle, an indigenous breed native to West Java, Indonesia, demonstrate significant adaptability and reproductive potential. However, their declining populations pose a threat to genetic conservation. Effective estrus synchronization is essential for enhancing reproductive efficiency and supporting fixed-time artificial insemination (FTAI) programs. Vaginal cytology profiling offers a reliable, noninvasive method for assessing estrus by evaluating the dynamics of epithelial and leukocyte cells, which reflect hormonal fluctuations. This study was aimed to investigate the cytological dynamics of vaginal epithelial, leukocyte cells and estrus response in Pasundan heifers subjected to double injection of prostaglandin F₂α (PGF₂α) and gonadotropin-releasing hormone (GnRH) synchronization. Nine Pasundan heifers, aged 1.5–2.0 years, were treated with PGF₂α with 2.75 μg/kg BW on days 0 and 11, followed by 2 μg/kg BW GnRH on day 12. Vaginal smears were collected daily from days 0 to 15, stained with 5% Giemsa, and examined microscopically to determine the proportions of parabasal, intermediate, superficial, keratinized, and leukocyte cells. The results indicated that the initial cytology showed a luteal phase dominated by parabasal (31.2%) and intermediate (30.6%) cells. Following hormonal treatment, superficial cells peaked at 70.9% on day 13, indicating estrus and estrogen dominance. By days 14–15, keratinized and parabasal cells had increased, confirming post-ovulatory luteal activity. The protocol achieved complete (100%) estrus synchronization among all heifers. It can be concluded that the double PGF₂ α-GnRH protocol effectively synchronized estrus in Pasundan heifers. Vaginal cytology has proven to be a sensitive and practical tool for monitoring reproductive phases, thereby supporting breeding management and conservation of this native genetic resource.